Metal oxide nanoparticles and their applications in nanotechnology - Chavali, Murthy S.; Nikolova, Maria P. (SN applied sciences, 2019)
Considering metal oxide nanoparticles as important technological materials, authors provide a comprehensive review of researches on metal oxide nanoparticles, their synthetic strategies, and techniques, nanoscale physicochemical properties, defining specific industrial applications in the various fields of applied nanotechnology. This work expansively reviews the recent developments of semiconducting metal oxide gas sensors for environmental gases including CO 2 , O 2 , O 3 , and NH 3 ; highly toxic gases including CO, H 2 S, and NO 2 ; combustible gases such as CH 4 , H 2 , and liquefied petroleum gas; and volatile organic compounds gases. The gas sensing properties of different metal oxides nanoparticles towards specific target gases have been individually discussed. Promising metal oxide nanoparticles for sensitive and selective detection of each gas have been identified. This review also categorizes metal oxides sensors by analyte gas and also summarizes the major techniques and synthesis strategies used in nanotechnology. Additionally, strategies, sensing mechanisms and related applications of semiconducting metal oxide materials are also discussed in detail. Related applications are innumerable trace to ultratrace-level gas sensors, batteries, magnetic storage media, various types of solar cells, metal oxide nanoparticles applications in catalysis, energy conversion, and antennas (including microstrip and patch-type optically transparent antennas), rectifiers, optoelectronic, and electronics.